1994
DOI: 10.1001/archsurg.1994.01420300051007
|View full text |Cite
|
Sign up to set email alerts
|

Is Barrett's Metaplasia the Source of Adenocarcinomas of the Cardia?

Abstract: Adenocarcinomas located at the gastroesophageal junction were associated with Barrett's metaplasia in nearly one half of the patients. The length of the Barrett segment tends to be short and may be missed during endoscopy. The presence of high-grade dysplasia within Barrett's mucosa supports a barrett's origin for half of the adenocarcinomas arising at this location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
118
1
6

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(135 citation statements)
references
References 25 publications
10
118
1
6
Order By: Relevance
“…EGJ-type tumors appear to be not related to this pathway, and they expressed p53 protein. These characteristics are similar to those of cardia adenocarcinoma in Western patients, but in our series, Barrett's metaplasia was detected in only two patients (3.8%), and the frequency of Barrett's metaplasia is much less in Japanese than in Western people (13%-42%) [18][19][20]. In the present study of small Siewert type II junctional cancers, the number of tumors that did not cross the EGJ (bEGJ-type) was larger than the number that did (EGJ-type).…”
Section: Discussionsupporting
confidence: 79%
“…EGJ-type tumors appear to be not related to this pathway, and they expressed p53 protein. These characteristics are similar to those of cardia adenocarcinoma in Western patients, but in our series, Barrett's metaplasia was detected in only two patients (3.8%), and the frequency of Barrett's metaplasia is much less in Japanese than in Western people (13%-42%) [18][19][20]. In the present study of small Siewert type II junctional cancers, the number of tumors that did not cross the EGJ (bEGJ-type) was larger than the number that did (EGJ-type).…”
Section: Discussionsupporting
confidence: 79%
“…Several previous reports have described a greater tendency of C-Ca than D-Ca towards deeper wall penetration, lymph node metastasis and poor prognosis, indicating that C-Ca may be a more aggressive tumour than D-Ca (Kalish et al, 1984;Wang et al, 1986;MacDonald and MacDonald, 1987;Hamilton et al, 1988;Clark et al, 1994;Ohno et al, 1995;Siewert and Stein, 1996;Kajiyama et al, 1997;Pinheiro et al, 1999;Tajima et al, 2001a). In this study, C-Ca was associated with a significantly higher prevalence of LVI than D-Ca.…”
Section: Discussionsupporting
confidence: 58%
“…It is associated with reflux symptoms, predominance in white males and a greater frequency of differentiated-type tumours as compared with adenocarcinoma of the distal stomach (D-Ca). It has also been described to show a greater tendency towards deeper wall penetration, lymph node metastasis, and a poor prognosis (Kalish et al, 1984;Wang et al, 1986;MacDonald and MacDonald, 1987;Hamilton et al, 1988;Clark et al, 1994;Ohno et al, 1995;Siewert and Stein, 1996;Kajiyama et al, 1997;Pinheiro et al, 1999;Tajima et al, 2001a). We have previously reported that early-stage of C-Ca is associated with higher frequency of gastric phenotypic marker expression and lower frequency of intestinal metaplasia of the surrounding mucosa as compared with early-stage of D-Ca (Tajima et al, 2001a).…”
mentioning
confidence: 76%
“…adenocarcinoma of oesophago-gastric junction (Antonioli and Goldman, 1982;Meyers et al, 1987;Hesketh et al, 1989;Powell and McConkey, 1990;Blot et al, 1991;Pera et al, 1993;McKinney et al, 1995). Similarities in terms of histopathology and epidemiological trends have been identified (Kalish et al, 1984;Wang et al, 1986;MacDonald and MacDonald, 1987;Powell and McConkey, 1992;Heidl et al, 1993;Siewert and Stein, 1998) and have led some observers to consider the two cancers as one disease with similar aetiologies (Clark et al, 1994).…”
mentioning
confidence: 98%